(untitled) (Global Journal of Human-Social Science, 2019)
Much of contemporary criticism of Ibsen plays has examined one of two concerns: Ibsen and Feminism, or Ibsen as a realist and a pioneer of modern theatre and drama. Articles on the first matter are often critical of universalizing readings of Ibsen that would have the dramatist concerned with the ills of humanity; articles on the latter theme tend to rejoice Ibsen’s assumed anti-theatrical overcoming of melodrama. Both topics can be found in his masterpiece The Wild Duck which is more honoured and received well in the study more than the other plays. Like Hamlet, The Wild Duck can be interpreted by each one in his own image; one day it will be read as a tragedy or tragicomedy, the next as the harshest irony; parts of it are clumsy, in other parts are embedded old controversies of that time. So searching yet so delicate is the touch, that these flaws and notions seem in themselves to strengthen the play. In this work, Ibsen perfected his own special power to infuse the particular, dull, limited fact with a halo and a glory. This paper is an attempt to examine the tension between illusion and reality in the play.